Exploring the effect of a sensory-based intervention on occupational participation and anxiety in child victims of trauma within the South African context - Joseph, Rowena Y (My University, 2022)
Within the South African context, sensory-based interventions in Child Victims of Trauma (CVT) could have a positive impact on occupational participation and levels of anxiety in this vulnerable group of our population by addressing emotional and developmental dysregulation which results in dysfunction in many occupations. Research indicates that self-regulation difficulties present as behavioural and emotional dysregulation in CVT. This is synonymous with the diagnosis of a sensory modulation dysfunction i.e. one’s inability to respond adaptively to sensation over a broad range of intensity and duration (Kramer and Hinojosa, 2010; Lane, 2002). According to literature talk therapy or top-down approaches, alone, do not address this need. Neuroscience research studies indicate that in CVT, the Broca’s area (speech area) becomes disengaged due to the intense and violent impact of trauma 13 on the nervous system, making top-down or talk therapy approaches difficult. The literature reviewed indicated that the behavioural and emotional difficulties experienced by CVT stems from physiological (body functions) responses that are linked to our autonomic nervous system. Therefore, the current study focused on exploring the effectiveness of a sensory-based intervention (bottom-up approach) to address the behavioural and emotional difficulties of CVT. Due to the occupational therapy profession being at the forefront of bottom-up therapy strategies and programmes, it was necessary to provide empirically based research to enhance therapists’ expertise in this field of practice. In Phase 1 a scoping review was applied to map the extent of empirical research available that identified and treated CVT using sensory-based interventions (based on Ayres Sensory Integration ®). In Phase 2, using purposive sampling, CVT from four residential care sites were selected. The Child Sensory Profile™ 2 (CSP™2), was completed by Child and Youth Care Workers (CYCWs). This formed the baseline assessment for 128 child participants. In Phase 3, a RCT was used incorporating two outcome measures for occupational performance and anxiety as the dependent variables, and the Alert Program® (a sensory-based intervention) as the independent variable. The results of the scoping review in Phase 1 yielded 13 articles, indicating that limited empirical research was available which focused on the identification and treatment of CVT using sensory-based interventions. The findings advocated for a multidisciplinary approach with sensory-based interventions being an important component in the treatment plan for CVT. The results of Phase 2 identified 91.4 % (117) child participants with sensory modulation dysfunction, with only 8.6 % (11) participants displaying no symptoms and scoring “just like the majority of others” in all categories of the summary scores on the CSP™ 2. For this sample of CVT, a unique sensory profile that differs from published norms for typical children “just like the majority of others,” indicated a vigilant sensory subtype with increased Sensitivity and Avoidance. In Phase 3 the RCT results, following nine weekly sessions of the Alert Program®, indicated greater statistically and clinically significant changes in anxiety levels as compared to changes in occupational participation. Various confounding variables impacted on the intervention process and outcome measures. A major limitation to the improvement across these outcome measures was the lack of adult availability to carry over and support self-regulation strategies in the daily lives of child participants. A pilot study prior to implementation of a sensory-based intervention is strongly recommended to ensure that child participants have consistent adult support to incorporate appropriate self-regulation strategies into their daily activities. This might enable them to manage their behaviours and emotions in appropriate ways which may have a significant impact on their occupational participation and levels of anxiety in their daily lives. Ongoing empirical research is also recommended to add rigour and credibility to this new field of research.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022